Dementia and mild cognitive impairment in prisoners aged over 50 years in England and Wales: a mixed-methods study - Katrina Forsyth; Leanne Heathcote; Jane Senior; Baber Malik; Rachel Meacock; Katherine Perryman; Sue Tucker; Rachel Domone; Matthew Carr; Helen Hayes; Roger Webb; Laura Archer-Power; et al. (National Institute for Health Research, 2020)
Background: People aged ≥ 50 years constitute the fastest-growing group in the prison population of England and Wales. This population has complex health and social care needs. There is currently no national strategy to guide the development of the many-faceted services required for this vulnerable population; therefore, prisons are responding to the issue with a range of local initiatives that are untested and often susceptible to failure if they are not fully embedded in and securely funded as part of commissioned services. Objectives: The objectives were to establish the prevalence of dementia and mild cognitive impairment in prisoners in England and Wales and their health and social care needs; validate the six-item cognitive impairment test for routine use in prisons to aid early and consistent identification of older prisoners with possible dementia or mild cognitive impairment; identify gaps in current service provision; understand the first-hand experiences of prisoners living with dementia and mild cognitive impairment; develop a care pathway for prisoners with dementia and mild cognitive impairment; develop dementia and mild cognitive impairment training packages for staff and prisoners; and produce health economic costings for the care pathway and training packages. Design: This was a mixed-methods study. Setting: The study setting was prisons in England and Wales. Participants: Prisoners aged ≥ 50 years and multiagency staff working in prison discipline and health and social care services took part. Results: Quantitative research estimated that the prevalence rate of suspected dementia and mild cognitive impairment in the prison population of England and Wales is 8%. This equates to 1090 individuals. Only two people (3%) in our sample had a relevant diagnosis in their health-care notes, suggesting current under-recognition of these conditions. The prevalence rate in prisons was approximately two times higher among individuals aged 60-69 years and four times higher among those aged ≥ 70 years than among those in the same age groups living in the community. The Montreal Cognitive Assessment screening test was found to be more effective than the six-item cognitive impairment test assessment in the older prisoner population. Qualitative research determined that staff and prisoners lacked training in knowledge and awareness of dementia and mild cognitive impairment, and this leads to problematic behaviour being viewed as a disciplinary issue rather than a health issue. Local initiatives to improve the lives of prisoners with dementia and mild cognitive impairment are often disadvantaged by not being part of commissioned services, making them difficult to sustain. Multidisciplinary working is hampered by agencies continuing to work in silos, with inadequate communication across professional boundaries. A step-by-step care pathway for prisoners with dementia and mild cognitive impairment was developed, and two tiers of training materials were produced for staff and prisoners. Limitations: Our prevalence rate was based on the results of a standardised assessment tool, rather than on clinical diagnosis by a mental health professional, and therefore it may represent an overestimation. Furthermore, we were unable to distinguish subcategories of dementia. We were also unable to distinguish between a likely diagnosis of dementia and other conditions presenting with mild cognitive impairment, including learning disability, severe depression and hearing impairment. Questionnaires regarding current service provision were collected over an extended period of time, so they do not reflect a 'snapshot' of service provision at a particular point. Conclusions: We hypothesise that implementing the step-by-step care pathway and the training resources developed in this study will improve the care of older prisoners with dementia and mild cognitive impairment. Future work: The care pathway and training materials should be evaluated in situ. Alternatives to prison for those with dementia or mild cognitive impairment should be developed and evaluated. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 27. See the NIHR Journals Library website for further project information.